2015 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) Proceedings 2015
DOI: 10.1109/i2mtc.2015.7151498
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and magnetic properties characterization of magnetic nanoparticles

Abstract: This paper deals with the characterization of magnetic iron oxide nanoparticles. Pure magnetite (Fe3O4) and noble metal doped magnetite were synthesized following a new sustainable microwave-assisted method. Furthermore, an experimental analysis was carried out to investigate the chemical and magnetic properties of these new nanopowders. Morphological and chemical characteristics of the pure magnetite and magnetite modified by noble metals such as palladium, platinum and ruthenium are provided together with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
(8 reference statements)
2
17
0
Order By: Relevance
“…The XRD pattern of iron oxide samples also showed that the material had good crystallinity. Peaks at 2Θ of 30.20, 35.60, 43.20, 54.00 and 57.35 corresponding to (220), (311), (400), (422) and (511), were in the accordance with Fe 3 O 4 structures (Bertolucci et al 2015). The peaks at 2Θ of 24.10, 33.10, 40.80 and 50.15 corresponded to (012), (104), (440) and (024) and were characteristic for the Fe 2 O 3 phase (Aliahmad and Nasiri Moghaddam 2013;Han et al 2014).…”
Section: Effect Of Mass Ratio Of Feo Fe 2 O 3 and Zno Nps On Magnetimentioning
confidence: 66%
“…The XRD pattern of iron oxide samples also showed that the material had good crystallinity. Peaks at 2Θ of 30.20, 35.60, 43.20, 54.00 and 57.35 corresponding to (220), (311), (400), (422) and (511), were in the accordance with Fe 3 O 4 structures (Bertolucci et al 2015). The peaks at 2Θ of 24.10, 33.10, 40.80 and 50.15 corresponded to (012), (104), (440) and (024) and were characteristic for the Fe 2 O 3 phase (Aliahmad and Nasiri Moghaddam 2013;Han et al 2014).…”
Section: Effect Of Mass Ratio Of Feo Fe 2 O 3 and Zno Nps On Magnetimentioning
confidence: 66%
“…The peaks observed between 630 and 580 cm −1 could be assigned to the stretching vibration of the Fe-O bond in the crystalline lattice of magnetite (Fe 3 O 4 ). Furthermore, although the literature shows no bonds above 600 cm −1 [ 74 ], new absorption bands with noticeable intensity located around 1627 and 1390 cm −1 , in addition to other peaks at 1285 and 1085 cm −1 with lower intensity, appear in the Fe 3 O 4 FTIR spectra [ 75 ]. In addition, the stretching vibration of Fe-O of the tetrahedral iron atom in Fe 3 O 4 appears around 620 cm −1 [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the stretching vibration of Fe-O of the tetrahedral iron atom in Fe 3 O 4 appears around 620 cm −1 [ 76 ]. However, the presence of peculiar bonds in the range of 740–620 cm −1 could be attributed to the maghemite phase (γ-Fe 2 O 3 ) [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…So, the superparamagnetic magnetite particles doped with precious metals, including platinum, may be used as an effective agent for diagnostic and anticancer therapy [1]. The formation of magnetite particles in the presence of noble metal cations results in the changes of magnetic characteristics of the samples, their morphology, physical and chemical properties as well [2].…”
Section: Introductionmentioning
confidence: 99%